Current Profile of Vivax Malaria in Isolated Area of Kualuh Leidong - Pasaribu, Ayodhia Pitaloka; Jimanto, Vincent; Ainur, Framita (Institute of Topical Disease Universitas Airlangga, 2025)
The Indonesian Ministry of Health targets to eliminate malaria by 2030. Vivax malaria, a challenging variant to eradicate, is prevalent in areas near elimination, including North Sumatra, which ranks fourth in malaria cases in Indonesia. Labura district, a part of North Sumatra, had a low-endemic status until 2020. However, an increase in cases occurred in 2021 within the Kualuh Leidong subdistrict, the primary contributor to Labura's malaria cases. This shifted the endemicity status from low to moderate. The objective of the study is to assess the malaria case profile in this region. A descriptive approach was used, employing a total sampling method at Tanjung Leidong Health Center between September 2022 and July 2023. This observational study identified 494 vivax malaria cases. Predominantly affecting males (60.9%), cases peaked in adults (>18 years) with 314 cases (63.6%). Microscopic examination was the leading diagnostic tool, used in 463 cases (93.7%). The health center primarily administered national regimen therapies dihydroartemisinin-piperaquine (DHP) + primaquine in 204 cases (62.4%), whereas others received alternate therapies. All patients recovered without referrals. Over 11 months, seven recurrence cases emerged, with five receiving quinine+primaquine. Vivax malaria cases in Kualuh Leidong have seen a significant increase compared to previous years. The attention and collaboration of all parties, both from the health center and the community, are necessary to achieve malaria elimination by 2030.